It’s not all about the profit: an analysis of changes in arts and business relations - Lewandowska, Kamila (Economics and Business Review, 2016)
Arts and business relationships have been generally characterised by sponsorship and philanthropy and there are a number of studies that support this binary approach. Recently however more research and experimentation has been conducted regarding the structural changes in the arts and business relations, e.g. the emergence of various new types of arts and business collaboration, such as arts-based methods. That being said there remains a dearth of exhaustive studies that would empirically analyse these new types of collaboration and how they influence the terrain of arts and business relations. My empirical study of thirty-three arts and business organisations is one of the few studies to emphasise the changes and transitions that shape the landscape of the arts and business field today. This exploratory study recognises and describes the transition from a transactional to a more partnership-oriented approach of arts and business organisations.